Living Out Loud : An Introduction to LGBTQ History, Society, and Culture - Murphy, Michael J.; Bjorngaard, Brytton; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Living Out Loud: An Introduction to LGBTQ History, Society, and Culture offers students an evidence-based foundation in the interdisciplinary field of LGBTQ Studies. Chapters on history, diversity, dating/relationships, education, sexual health, and globalization reflect current research and thinking in the social sciences, humanities, and sciences. Coverage of current events and recommendations for additional readings, videos, and web resources help students apply the contents in their lives, making Living Out Loud the perfect core text for LGBTQ+ Studies (and similar) courses.
Chapter One: Out of the Past: Histories, byChristianne Anastasia Gadd; -- Chapter Two: Same Difference: Diversities, by Michael J. Murphy; -- Chapter Three: Getting It On: Sexual Behaviorand Sexual Health, byMichael J. Murphy; -- Chapter Four: Together, Forever?: Relationships,by Christine Smith and Joel A. Muraco; -- Chapter Five: Reading, Writing, Queering: Education, byElizabeth Dinkins and Patrick Englert; -- Chapter Six: Were Here! Were Queer!: Power, Politics,and Activism, byGeorge A. Waller; -- Chapter Seven: Pop Out!: Mass Media & Popular Culture, byByron Lee; -- Chapter Eight: Signifying Queerness: Literatureand Visual Arts, bySusan K. Thomas and William J. Simmons; -- Chapter Nine: Getting Around: Globalizationand Transnationalism, byEvan Litwack
Includes bibliographical references and index.
Also available in print format.
Keywords: SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Gender Studies; Gays -- History; Sexual minorities -- History; Gays; Sexual minorities; Electronic books